Outcome of different treatment regimens used in newly diagnosed ITP pediatric patients - Mervat El-Sayed Haroun; Rasha Abd El-Raouf; Nesreen Mostafa Habib (SpringerOpen, 2018)
Aim of the study: To compare the efficacy of different treatment options for newly diagnosed ITP in pediatrics. Patients and methods: This is a retrospective observational study that reviewed data of 102 newly diagnosed ITP children. Treatment regimens received by patients were classified into 5 types: Type I: pulse intravenous methylprednisolone followed by oral prednisolone then gradual tapering. Type II: oral prednisolone 4 mg/kg/d × 4 days. Type III: oral prednisolone 2 mg/kg/d followed by gradual tapering. Type IV: intravenous immune globulin (IVIG) combined with intravenous methylprednisolone. Type V: no treatment. Platelet counts at presentation, after 1 week, at 1 month, 3 months and 6 months from initial presentation were analyzed. Results: Patients who received Type I, III or IV treatment showed statistically significant higher response to treatment at 1 week (96.1%, 93.3%, and 100% respectively) in comparison to those who received Type II or no treatment (Type V) in which less response was observed (58.8% and 75% respectively); (p-value = 0.001%). However, the overall response showed no statistically significant difference in response to treatment using different types of treatment at one month and 3 months, p-value = 0.086 and 0.335 respectively. When we evaluated the response overtime of each line of treatment at 3 months, Type I showed a statistically significant response (p = 0.009) with the biggest number of patients continuing to maintain response up to 3 months. Conclusion: We recommend the use of (methylprednisolone 20-30 mg/kg/d × 3-5 days) followed by oral (prednisolone 2 mg/kg/d) due to rapid and sustained response. Keywords: Purpura, Thrombocytopenia, Idiopathic, Methylprednisolone, Immunoglobulins, Intravenous, Prednisolone